PENERAPAN TERAPI NON FARMAKOLOGI DEEP BREATHING UNTUK MENINGKATKAN POLA NAFAS PADA PASIEN PNEUMOTORAKS DI RUANGAN IGD RS IBNU SINA MAKASSAR - Nurul Aulia; Rahmat Hidayat; Fitria; Haeril Amir (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Pneumothorax is a respiratory emergency condition due to the entry of air into the pleural cavity that causes lung collapse, ventilation obstruction, and ineffective breathing patterns. Non-pharmacological therapies such as deep breathing can help improve lung ventilation, alveolar expansion, and decrease shortness of breath. This study aims to determine the effectiveness of deep breathing therapy in improving breathing patterns in pneumothorax patients at Ibnu Sina Hospital Makassar. Case study research was conducted on one patient with a medical diagnosis of pneumothorax. Data were obtained through interviews, observations, and physical examinations. Deep breathing interventions were given for 3 sessions, each lasting 3–4 seconds during treatment in the emergency room. After therapy, the breathing rate decreased from 28x/min to 24x/min, oxygen saturation increased from 89% to 91%, the use of the breathing support muscles was reduced, and the patient appeared calmer. However, the increase in oxygenation is relatively small, so deep breathing needs to be collaborated with additional oxygen for optimal effect. Deep breathing is effective as a complementary intervention to improve breathing patterns, but it cannot be the primary therapy. This therapy should be done in conjunction with oxygenation to support physiological improvement and patient comfort